2015
DOI: 10.1021/acs.orglett.5b02027
|View full text |Cite
|
Sign up to set email alerts
|

Spirobifluorene-2,7-dicarbazole-4′-phosphine Oxide as Host for High-Performance Single-Layer Green Phosphorescent OLED Devices

Abstract: A new host material based on the 2,7,4'-substituted spirobifluorene platform has been designed and used in single-layer phosphorescent OLED with very high efficiency (EQE = 13.2%) and low turn-on voltage (2.4 V). This performance is among the best reported for green single-layer PhOLEDs and may open new avenues in the design of host materials for single-layer devices.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
56
0
4

Year Published

2017
2017
2021
2021

Publication Types

Select...
8
1

Relationship

5
4

Authors

Journals

citations
Cited by 63 publications
(61 citation statements)
references
References 23 publications
1
56
0
4
Order By: Relevance
“…It should be stressed that these blue PhOLEDs performances remain modest compared to the best recently reported for pure hydrocarbons. [17] However, with a more accurate design (incorporation of donor and/or acceptor units), [15,41] device performance could be easily increased and this new family of 1-substituted SBF can play an interesting role in the future. CONCLUSION To summarize, this work reports the first rational study on SBF regioisomerism, highlighting the chief influence of the bridge and of the linkages on the electronic properties.…”
Section: Scheme 1 Synthetic Routes To 1 Andmentioning
confidence: 99%
See 1 more Smart Citation
“…It should be stressed that these blue PhOLEDs performances remain modest compared to the best recently reported for pure hydrocarbons. [17] However, with a more accurate design (incorporation of donor and/or acceptor units), [15,41] device performance could be easily increased and this new family of 1-substituted SBF can play an interesting role in the future. CONCLUSION To summarize, this work reports the first rational study on SBF regioisomerism, highlighting the chief influence of the bridge and of the linkages on the electronic properties.…”
Section: Scheme 1 Synthetic Routes To 1 Andmentioning
confidence: 99%
“…Indeed, in order to obtain a high triplet energy (E T ), key feature in the design of host materials for blue PhOLEDs, which are still the weakest link of this technology, it is mandatory to restrict the π-electrons delocalization within the OSC. This π-conjugation disruption has been successfully investigated with ortho linked SBFs (substitution in position 4) [12][13][14][15][16] and meta linked SBFs (substitution in position 3), [2,[17][18][19][20] leading to high performance blue PhOLEDs. However and despite the recent very high efficiency devices obtained by Jiang et al, [17] and by our groups [15] only few examples of 3-and 4-substituted SBFs have been described to date and more importantly no rational structure-properties relationship studies have been reported on SBF regioisomerism.…”
Section: Introductionmentioning
confidence: 99%
“…[32][33][34][35] As it is known that the increase of HOMO energy levels through the incorporation of phenylacridine, [36][37][38][39] indoloacridine, [40][41][42] quinolinophenothiazine 43 or quinolinophenoxazine 44 moieties instead of a fluorene core has remarkable consequences on the device performance we wish to report herein the first examples of 4-substituted SBF derivatives incorporating electronrich fragments, namely N-phenylcarbazole in 4-PhCz-SBF and trimethoxyphenyl in 4-Ph(OMe) 3 -SBF, Scheme 1. Through a detailed structure-properties relationship study with the corresponding building blocks, namely 4-phenyl-spirobifluorene (4-Ph-SBF), spirobifluorene (SBF), 1,2,3-trimethoxybenzene (Ph(OMe) 3 ) and N-phenyl-carbazole (N-PhCz), we highlight herein the remarkable influence of the C4-substituent on the electronic properties.…”
Section: Chartmentioning
confidence: 99%
“…The exponential development of organic electronic leads to an always growing demand of new, highly efficient organic semiconductors (OSCs) adapted to their use in specific devices 1 including organic light-emitting diodes (OLED) based on fluorescent emitting materials, [2][3][4][5][6][7][8] or based on phosphorescent materials, [9][10][11][12][13][14][15][16][17][18][19] organic field-effect transistor (OFET) [20][21][22][23][24] or organic photovoltaic (OPV). 1,25 Historically, in the field of OFETs, the design of p-type materials (hole-transporting) such as pentacene, 26 oligothiophene 27 or bridged oligoarylene [28][29] 33 (see 1-4 structures in Chart 1).…”
Section: Introductionmentioning
confidence: 99%